Bone marrow stromal cells implantation and suture repair of peripheral nerve: a comparative study of functional, histopathological, morphometric and relative gastrocnemius muscle weight in rabbits - Al-Timmemi, Hameed A.; Ibrahim, Rashid; Abu Bakar @ Zakaria, Md Zuki; Tengku Ibrahim, Tengku Azmi; Al-Jashamy, Karim Alwan Mohamed (Academic Journals, 2011)
The peripheral nervous system has the ability to regenerate after injury. Peripheral nerve injuries are caused by penetrating injury, crush, traction and ischemia compression. However, the availability of various nerve coaptation and other techniques for the attainment of functional nerve regeneration is still inadequate. The objective of this study was to compare the effectiveness of bone marrow stromal cells (BMSCs) implantation and epineural nerve suture on peripheral nerve regeneration in a rabbit model. Ten male New Zealand white rabbits were divided into two groups. In the primary epineural repair group (control group), the left sciatic nerve was skeletonized from the sciatic notch to the point of bifurcation, with the nerve been transected at the mid-shaft of the femoral bone and repaired with six epineural sutures. In the treated group, the epineural repaired nerve was implanted with BMSCs in the proximal and distal segments of the transected sciatic nerve. Assessment of the nerve regeneration was based on functional (motor and sensory), histological and morphometric criteria, including the number of myelinated nerve fibers, nerve fiber diameter, axon diameter, myelin sheath thickness, g ratio and relative gastrocnemius muscle weight. The results of the examination showed that the treated group had the best regeneration and functional recovery.